Pharmacognostical And Phytochemical Analysis Of Kantakari Solanum Xanthocarpum (Schrad & Wendl.) - Dogra, Pooja; Murthy, A Rama; Nathani, Sumit (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda is one of the most ancient system of life, health and care. Indian Science of Medicine has the largest collection of medicinal plants. Kantakari Solanum Xanthocarpum (Schrad & Wendl.) of family Solanaceae is one of the ‘Dashmoola’ and used drug in Ayurveda. References about Kantakari are available since Vedic Kala, Samhita Kala, Madhyama Kala, Adhunika Kala. Ayurveda describes use of Kantakari in wide range of ailments like Kasa, Shwasa, Jwara, Pinasa, Parsvasoola etc. the drug is used as hepatoprotective, antiasthmatic, antioxidant, immunomodulatory, wound healing, antispermatogenic, antifertility, antipyretic, anticancer, anti-allergic, anthelmintic, antimicrobial. The phytochemical studies revealed the presence of active constituents, carbohydrates, amino acid, steroids, proteins, saponins, alkaloids, glycosides, and tannins in aqueous and alcoholic extracts.